CYTOKINE RESPONSE IN PERI-IMPLANTITIS - S. N. Gontarev; I. S. Gontareva; R. R. R. Kassar; A. A. Bogdanova; V. E. Farafonov (Медицинская иммунология)
AbstractImplants are currently widely used in dentistry and effectively provide lost teeth. However, in the presence of concomitant risk factors and low oral immunity, patients develop peri-implantitis, accompanied by inflammation and an immune response of the body, while the cytokine profile in saliva remains insufficiently studied. The purpose of this study was to study the cytokine response and evaluate the diagnostic information content of pro-inflammatory and anti-inflammatory cytokines in patients with peri-implantitis. 65 patients with reimplantations aged 50-65 years and 48 patients aged 50-65 years without reimplantations were examined. The diagnosis of reimplantations was carried out based on the results of a clinical examination, the presence of symptoms - bleeding during probing, suppuration during probing, bone loss on radiographs ≥ 3 mm and the depth of the probed pocket ≥ 6 mm. In saliva collected in the morning on an empty stomach, the content of a number of pro-inflammatory and anti-inflammatory cytokines was determined by enzyme immunoassay using Protein Contour kits (St. Petersburg). The cytokine profile of patients with peri-implantitis is characterized by the expression of both pro-inflammatory and anti-inflammatory cytokines. The saliva content of IL-1 increased particularly among patients with peri-implantitis to 205,9±4,2 pg/ml versus 67,5±3,1 pg/ml in participants without peri-implantitis, IL-6 to 29,4±1,3pg/ml versus 11,7±1,2 pg/ml, respectively, with a significant difference in all cases. In addition, the level of IL-19 increased to 54,9±2,3 pg/ml relative to the comparison group – 30,5±1,4pg/ml, TNF-α – to 202,4±3,8 pg/ml relative to 115,6±2,4 pg/ml, respectively (p<0,001). Along with this, the saliva concentration of patients with IL-4 and IL-10 peri-implantitis increased significantly to 18,2±1,4 pg/ml versus 3,8±0,6 pg/ml in the group without peri-implantations and to 66,5±2,7 pg/ml versus 15,3±0,9 pg/ml, respectively (p<0,001). The calculation of the Kullback information measure revealed the highest diagnostic information content for IL-4 (8,5), IL-10 (8,1), IL-1b (5,7), IL-6 (4,2). To objectify diagnostic criteria, it is recommended to use the levels of IL-4, IL-10, IL-1b and IL-6 established in saliva.